2018
DOI: 10.1007/s10570-018-1983-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial cellulose nanofiber-based films incorporating gelatin hydrolysate from tilapia skin: production, characterization and cytotoxicity assessment

Abstract: In this work, films based on bacterial cellulose nanofibers (BCNFs) incorporating gelatin hydrolysate (GH) from tilapia skin were produced. The effect of plasticizer (sorbitol or glycerol) and GH incorporation was evaluated on the physical-chemical and optical properties of films. BCNFs were produced using bacterial cellulose obtained from Hestrin and Schramm (HS) medium (BCNF-HS) or cashew apple juice (BCNF-CM), which was studied as an alternative to HS. Films with sorbitol showed the best properties and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 85 publications
1
9
0
Order By: Relevance
“…5), whereas 70% of cell viability is considered the threshold for non-toxicity (ISO 10993-1). So, the films and their components did not produce any cytotoxic effect on those cells, corroborating previous results from materials containing NFBC (Lima et al, 2018;Padrão et al, 2016) and CG (Abreu et al, 2016).…”
Section: Cytotoxicity Of Filmssupporting
confidence: 90%
“…5), whereas 70% of cell viability is considered the threshold for non-toxicity (ISO 10993-1). So, the films and their components did not produce any cytotoxic effect on those cells, corroborating previous results from materials containing NFBC (Lima et al, 2018;Padrão et al, 2016) and CG (Abreu et al, 2016).…”
Section: Cytotoxicity Of Filmssupporting
confidence: 90%
“…After physical entrapment of plant-based proteins inside BC, WCAs were increased significantly. The increased WCAs could be attributed to the formation of hydrogen bonding between BC fibers and plantbased proteins, reducing the number of free hydroxyl groups, and thus increasing the hydrophobicity of BC bio-leather (Lima et al 2018). It was also found that BC entrapped with both protein and glycerol had improved WCA than BC entrapped with protein only.…”
Section: Water Resistancementioning
confidence: 92%
“…The PH was obtained by applying the methodology proposed by Nikoo et al (2014) and modified by Lima et al (2018), at the Biochemistry Laboratory of the Center of Technology and Food Agribusiness-Agricultural Research Company (EMBRAPA), Brazil. The process comprises the hydrolysis of commercial fish gelatin (Brazilian Ministry of Health registration: 6.6660.0006), composed of proteins derived from different fish species by-products.…”
Section: Commercial Fish Gelatin Hydrolysate Preparationmentioning
confidence: 99%